Design ambipolar conductivity on wide-gap semiconductors: The case of Al- and Na-doped CaS. (15th November 2022) - Chen, Yu; Fan, S.W.; Gao, G.Y.
Abstract: Transparent conducting materials (TCMs) can be divided into n-type and p-type conductivities. For wide gap semiconductors, it is difficult to obtain two types conductivities in one material. Herein, based on the first-principles calculations, we predict the wide-gap semiconductor CaS is an ambipolar semiconductor. The n (p)- type conductivity can be realized via the Al (Na) substituting Ca (labeled as AlCa (NaCa )) defects under Ca (S)-rich condition. The thermodynamic simulations show as the growth temperature increases, the defect concentrations and carrier densities keep continuously rising, and the Fermi energy shifts toward band edges. After quenching the doped samples from high temperature to 300.0 K, the density of electron can reach 6.91×10 17 cm −3 under Ca-rich condition, and that is 1.23×10 16 cm −3 for hole under S-rich condition. High density of electron and hole, small electron and hole effective masses, together with the wide band gap indicate Al (Na)-doped CaS is a promising ambipolar transparent semiconductors. This study provides a new candidate to design and explore the ambipolar transparent conducting materials.